THE ROLE OF TRAINING OF THE COUNTRY BY THE TNI AT THE DISCIPLINE WORK EMPLOYEES IN THE PT. BERAU COAL KABUPATEN BERAU - Sari, Rina Febriana; Hardoko, A; Salamah, Alim (Unmul Civic Education Journal, 2021)
The purpose of this research is knowing the role of training of the country on the discipline work employee, include : disciplined time, disciplined regulations and dressed and disciplined responsibility. The of this research is thedescriptive kualitatif, with its primary data and secondary. The subject of research is the employees who followed training of the chosen with purposive sampling. Technique observations, collecting data is an interview and documentation. The techniques data analysis of the reduction of data, presenting data and the conclusion. The results of research suggests that training of the very act and give positive things in disciplined work employees at work, which can be in the value of discipline time is very disciplined 77%, disciplined 19% and quite disciplined 4%, the discipline regulations and dressed in which is very disciplined 90%, disciplined 10% and quite discipline 0%, the discipline responsibility is very disciplined 84% of discipline 14% and quite disciplined 2%. The results of research is reinforced with the documentation employees at the place of work, as well as the data from the informant showing work increasingly disciplined. With the training of the country, employees have the opportunity to absorb knowledge and the values of the new, so that employees can increase disciplined on while at work.